Microbiological Characteristics and Surgical Management of Animal-Bite-Related Oral & Maxillofacial Injuries: A Single Center’s Experience - Johannes Spille; Juliane Schulz; Dorothee Cäcilia Spille; Hendrik Naujokat; Henning Wieker; Jörg Wiltfang; Aydin Gülses (Antibiotics, 2021)
The objective of the current study is to retrospectively evaluate animal-bite injuries and to gain insight into the epidemiology, accident consequences and treatment concept of these accidents in oral and maxillofacial surgery. Data of patients, who were admitted January 2015 and April 2021, were retrospectively evaluated regarding the patients’ characteristics (age, gender), facial distribution of substance defects/partial amputations, duration of hospitalization, operation treatments and antibiotic treatments. Data of 75 patients were included. Patients were bitten by dogs (n = 69.92%), cats (n = 4) and horses (n = 2). Lower eyelid/cheek complex was the most affected region (n = 37, 32.74%). Most of the patients between 0 and 3 years had to be operated on under general anesthesia (p = 0.011), while most of the adults could be operated on under local anesthesia (p = 0.007). In the age group 0–12 years, 30 patients (68%) were operated on under general anesthesia. Ampicillin/Sulbactam (48%) was the antibiotic most used. Antibiotics were adjusted after wound swabs in case of wound infections or critical wound conditions. This means that resistant antibiotics were stopped, and sensitive antibiotics were used. Structured surgical and antibiotic management of animal-bite wounds in the maxillofacial region is the most important factor for medical care to avoid long-term aesthetic consequences. Public health actions and policies under the leadership of an interdisciplinary committee could improve primary wound management, healing outcome and information status in the general population.